Systematic review of patient reported outcomes from open tibia fractures in low and middle income countries - Schade, Alexander T.; Hind, Jamie; Khatri, Chetan; Metcalfe, Andrew J.; Harrison, William J. (Injury, 2020)
•The clinical history of open tibia fractures in low or middle income countries remains largely unknown in terms of patient reported outcomes.•Further studies are required to define these outcomes in open tibia fractures before best treatments can be assessed. Open tibia fractures are a common cause of admission following road traffic accidents in low and middle income countries (LMICs), resulting in substantial mortality and disability. It is important to summarise the clinical course of this injury using patient reported scores in order to assess best treatment in LMICs. To summarise the disability after sustaining an open tibia fracture in LMICs All studies were identified from a systematic search of Medline, Embase and the Cochrane Central Register of Controlled Trials. We included any human with a diagnosed open tibia fracture, following any intervention. Studies were performed in a low or middle income country. The primary outcome was any validated patient reported outcome score reported after three months. Secondary outcomes included economic impact and complications such as infection, non-union and amputation. Data was extracted and summarised. We reviewed 3,593 articles from our search. A total of 18 studies were included from 10 countries with 8 different outcome scores. The average age was 35 years old and 86% of the patients were male. Thirty-one percent were Gustilo I, 28% Gustilo II, 19% Gustilo IIIA, 17% Gustilo IIIB and 5% Gustilo IIIC. The most common complications reported were 18% infection, 15% non-union and 15% amputation. Economic impact was reported in only one study with 100% patients working pre-injury and 20% post-injury at 12 months. Mean follow-up duration for outcome scores was 19.8 months. There was heterogeneity between the studies in terms of subject of the studies, outcome criteria, fracture type, surgical technique and length of follow-up. Therefore, no meta-analysis could be performed. The clinical history of open tibia fractures in low or middle income countries remains largely unknown in terms of patient reported outcomes. Further studies are required to define these outcomes in open tibia fractures before best treatments can be assessed.